Estimasi Deviasi Parameter pada Motor DC Menggunakan Sliding-Mode Observer dan Algoritme Least-Square - Dzuhri Radityo Utomo; Muhammad Faris (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
Performing system/plant maintenance is very important as an attempt to avoid any failure during system/plant operation. One of the methods that can be adopted to detect any potential failure inside a plant is by estimating the value of the plant’s parameters. When the plant’s parameters deviate too far from their nominal values, the plant will be more likely to fail. In this paper, an estimation method for estimating the deviation in the parameters of a linear system/plant is proposed as an improvement of the previously proposed method. The main component of this parameter deviation estimator system was an observer block which adopted the sliding-mode observer in combination with an adaptive filter block. The adaptive filter block used in this system adopted the least-square algorithm instead of adopting the gradient-descent algorithm as in the previously proposed method. This method was simulated to estimate the deviation in the parameters of DC motor to verify the effectiveness of the proposed metho. The simulation results showed that this method could successfully estimate the deviation of DC motor parameters with a maximum estimation error of less than 4 %. This method could estimate the deviation in DC motor parameters for both constant deviation value and slowly-changing deviation value as time goes by. In addition, estimating the parameter deviation using this method could produce a good level of accuracy even when using a fairly low-frequency input signal. This method is suitable to be adopted in parameter monitoring process of a linear system so that any fault occurring in the system can be detected and isolated before the plant is fatally damaged.